Normalisation and the Translation of Phraseology in the COVALT Corpus - Marco, Josep (Meta, 2009)
AbstractIn this article, it is assumed that phraseological usage can be regarded as an indicator of normalisation in translated texts, as phraseological units are target-language standardised forms belonging to its lexical repertoire. Drawing on data yielded by the English-Catalan subcorpus of COVALT (Valencian Corpus of Translated Literature), it was found that Catalan translated texts are less phraseological than their corresponding English source texts, though only by a narrow margin. The narrowness of the margin seems to bear witness to some effort on the translators’ part to retain or recreate a noticeable degree of phraseological activity in translated texts. However, further research is needed into the motives underlying translator behaviour in this respect.